Responses of the Arabidopsis KNOX and Boron transport gene mutants against the deficiency and overdose of Boron nutrient - WIDI SUNARYO; NURHASANAH NURHASANAH (Society for Indonesian Biodiversity, 2016)
Sunaryo W, Nurhasanah. 2016. Responses of the Arabidopsis KNOX and Boron transport gene mutants against the deficiency and overdose of Boron nutrient. Biodiversitas 17: 218-221. Boron is a micro element essential to the plant. Deficiency or overdose of this element result in the stunted plant growth and leads to a decline in the quantity and quality of crop yield. This research was aimed to study the growth response of single homozygous mutant KNOX bp-9. Some seedling growth variables such as root length, leaf number and plant height were characterized to observe the response of plant against the treatments. Results showed that different concentration of Boron resulted in a significant effect to seedling growth of all mutants. The loss of BOR1 gene function as Boron transporter at bor1-1 mutant strains and loss of NIP5;1 gene function as Protein Channel caused severe growth pressures in conditions of media without boron mutants showed no significant growth differences compared to the wild type (Col-0) indicating that the KNOX genes does likely not related to the function of Boron transport genes.